Comparative Study of Car Seat Sales During and Before the 0% PPNBM Policy During the Covid-19 Pandemic at PT X - Rochayati Febriarhamadini; Ricky Prima (International Journal of Applied Research and Sustainable Sciences, 2023)
This research aims to find out the sales of car seats during the 0% PPnBM policy for the period March to December 2021 and to find out the sales of car seats before the 0% PPnBM policy for the period March to December 2020 and to find out the comparison of sales from of PT. when PPnBM was 0% for the period March to December 2021 and before the PPnBM policy was 0% for the period March to December 2020 at PT. Toyota Motor Manufacturing Indonesia. This research method uses documentation techniques in data collection. In documentation techniques, documents are records of past events, which can be in the form of writing, drawings or works. The data used by the author in this research is seat sales data (documentation) which data was obtained from the logistics division regarding car seat sales at PT. X. And using validity tests and descriptive statistics. The results of data processing obtained in a descriptive statistical manner are that there was a very good increase in sales of car seats when the PPnBM policy was 0% and the results of hypothesis testing using the t-difference test were that there was a significant difference in sales when the PPnBM policy was 0%. So it can be concluded that there is an average difference between car seat sales when PPnBM was 0% and car seat sales before PPnBM was 0%, which means there was an increase in car seat sales when the PPnBM policy was 0%.